ASYNCHRONOUS ONLINE COMMUNICATION OF THE LEARNING MANAGEMENT SYSTEM FOR STUDENTS’ WRITING ABILITY - Lilis Sholihah (Premise: Journal of English Education and Applied Linguistics, 2022)
The use of the Internet is one of the solutions to tackle the communication problems during the covid-19 pandemic. Online activity, which can be done to facilitate learning a language, especially English, is preferable to be synchronous and asynchronous online communication. This research focuses on using asynchronous online communication of the learning management system to enhance students' writing ability in pre-intermediate writing subjects during the covid-19 pandemic. The method of the research is a quantitative method with One-Group Pretest-posttest design. The research population is the second-semester students, and the sample of the research is pre-intermediate writing class C, which consists of 23 students. The data analysis results show that the student's average score on the pre-test is 76.96, and the mean score of the post-test is 79.83, which means that the mean score of the post-test is higher than the mean score of the pre-test. In other words, the gained score is 2.87. Wilcoxon test for non-parametric statistics is applied to decide the hypothesis. The calculation of the test statistic showed that the z test result is 2.62 with a 2-tailed significance is 0.009. It indicates that the result is significant since 0.009 is less than 0.05 (0.009 < 0.05). It means that the Null hypothesis (H0)  is rejected, while the Alternative hypothesis (H1)  is accepted. Therefore, it can be concluded that there is a significant effect of using asynchronous online communication of the learning management system (www.schoology.com) on students' writing ability. The study implies that this LMS model is visible in ELT, especially to improve the students' four skills, such as writing ability.